Philosophical Exploration into the Exceptionalities of Giftedness and Disability: Developing Frameworks for Understanding - Carroll, La Shun L. (Philosophy and Realistic Reflection, 2025)
This research explores the concept of asynchrony in human development, specifically the imbalance between mental and physical aging in relation to time. It posits that while chronological age progresses uniformly, intellectual development can accelerate, leading to giftedness, or decelerate, resulting in intellectual delays or disabilities. A unique manifestation of asynchrony is observed in accelerated physical aging, exemplified by Progeria, where individuals age at a disproportionately rapid pace. The study challenges the notion of time as a direct cause of aging, arguing that aging effects are correlated with time but not caused by it. The core argument is that effects, such as physical aging, cannot accelerate independently of their causes without disrupting our understanding of causality. Using the example of Progeria, the research suggests that the rapid aging observed is due to factors occurring during the passage of time, not time itself. The paper argues against the belief that the passage of time directly causes asynchronous effects of aging and intellect. It uses a thought experiment involving a firearm to illustrate the metaphysical implications of accelerated effects without corresponding acceleration of their causes. The research concludes that accepting asynchrony and the independent acceleration of effects necessitates a reevaluation of causality, which could fundamentally alter our understanding of the universe.